Visualization of ceramide channels in lysosomes following endogenous palmitoyl-ceramide accumulation as an initial step in the induction of necrosis - Yamane, Mototeru; Moriya, Shota; Kokuba, Hiroko (Biochemistry and biophysics reports, 2017)
In this study, we showed that the dual addition of glucosyl ceramide synthase and ceramidase inhibitors to A549 cell culture led to the possibility of ceramide channel formation via endogenous palmitoyl-ceramide accumulation with an increase in cholesterol contents in the lysosome membrane as an initial step prior to initiation of necrotic cell death. In addition, the dual addition led to black circular structures of 10-20 nm, interpreted as stain-filled cylindrical channels on transmission electron microscopy. The formation of palmitoyl-ceramide channels in the lysosome membrane causes the liberation of cathepsin B from lysosomes for necrotic cell death. On the other hand, necrotic cell death in the dual addition was not caused by oxidative stress or cathepsin B activity, and the cell death was free from the contribution of the translation of Bax protein to the lysosome membrane.